If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + 39 = 12 + -33 Reorder the terms: 39 + 4x = 12 + -33 Combine like terms: 12 + -33 = -21 39 + 4x = -21 Solving 39 + 4x = -21 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-39' to each side of the equation. 39 + -39 + 4x = -21 + -39 Combine like terms: 39 + -39 = 0 0 + 4x = -21 + -39 4x = -21 + -39 Combine like terms: -21 + -39 = -60 4x = -60 Divide each side by '4'. x = -15 Simplifying x = -15
| x/2+6=10 | | 2-4(h-4)=10(2h-3) | | 15m^6n+14m^5n^2+3m^4n^3= | | 0.2t=0.2+0.7t | | 2(1/3+4x/3)=4-3x | | 175000.00+550.00x=300440 | | 12g+1=8g+3 | | 6f+7=2f+3 | | x^2-4x-64=0 | | 2(1+4x/3)=4-3x | | 13+4g=16+2g | | 8600=80X+5000 | | 10n+49=-2+5(1+2n) | | CUBERT(2w+3)=CUBERT(w-2) | | 25x^2+6x=0 | | 2x+18=32 | | h^2-5h=50 | | 5+(y+2)=20 | | 0.9t=0.9+0.6t | | -12+9(b+1)=11(b+3)-8 | | 7z^2-49=0 | | 2x-5/12+x=2x+5/2+5 | | 6+x/2=2x | | 3q^2-12q=15 | | -39-8x=5(1-6x) | | 6+1/2x=2x | | -2m=2(1-5m)+6m | | y=3/4x+42.5 | | 5-(6-x)= | | x^4+8x^4=9x^4 | | 1996+43x=7385+67x | | 4x+3y^2=0 |